PENGARUH KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KOMPETENSI GURU YANG DI MODERASI ETOS KERJA DI SMK NEGERI 1 GEROKGAK - Dharma Hartawan, I Gusti Made; Ayunitri, Ketut Dyah (Komunitas Manajemen Kompetitif, 2024)
This research aims to determine the influence of the principal's leadership on teacher competency which is moderated by work ethic at SMK Negeri 1 Gerokgak. The method used in this research is quantitative using data obtained from questionnaires. The sample used was 59 people. The data analysis technique uses the Inner Model Analysis Technique. The results of the research show that: (1) Work Ethic has a positive and significant effect on Principal Leadership, (2) Principal Leadership has a positive and significant effect on Teacher Competency and (3) Work Ethic does not have a positive and significant effect on Principal Leadership Moderation on Competence Teacher.